2020
DOI: 10.3389/fneur.2020.00882
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Locomotor Dual-Task Interference in Stroke Survivors and the Influence of the Tasks: A Systematic Review

Abstract: Background: Walking in the community can be challenging for stroke survivors. The fact that community walking often requires performing another task while walking further adds to this challenge and can lead to a deterioration of performance in one or both tasks. Objective: To review the existing literature about cognitive-locomotor dual-task interference (DTI) magnitude and pattern while walking in patients with stroke and to explore the influence of tasks' nature on DTI. Moreover, this review investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 62 publications
3
27
1
3
Order By: Relevance
“…Dual-task phenomenon was extensively documented, but only a few studies have used cognitive and locomotor tasks representing daily activities. Indeed, commonly used cognitive tasks are adapted from traditional neuropsychological assessments, such as the Stroop test or serial subtractions [ 23 ]. Existing literature reflects upon the ecological validity of those executive function assessments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-task phenomenon was extensively documented, but only a few studies have used cognitive and locomotor tasks representing daily activities. Indeed, commonly used cognitive tasks are adapted from traditional neuropsychological assessments, such as the Stroop test or serial subtractions [ 23 ]. Existing literature reflects upon the ecological validity of those executive function assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Those assessments seemed inconsistent with the executive functions solicited when performing daily activities [ 24 ]. Regarding the locomotor task, participants were most frequently asked to walk forward over a short distance, without any mobile obstacles in most dual-task studies [ 12 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…At this point, within the context of a dual-task, the attentional demand associated with gait depends on various factors 8 , 10 , 12 , 15 that could account for the observed results. These factors could be regarded as possible explanations and as study limitation that we acknowledge.…”
Section: Discussionmentioning
confidence: 95%
“…with effects on cognitive task only ), (3) motor-related (i.e. with effects on locomotor task only ) or (4) absent 12 . In the present study, dual-task interference observed in both patients with axSpA and healthy controls can be placed in the class of ‘motor-related’ as the gait performance was significantly altered during dual-task walking and the performance of secondary manual task while walking remained maximal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation